2023
DOI: 10.3390/life13030659
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Differential Expression of MicroRNAs in the Human Skeletal Muscle with Distinct Fiber Type Composition

Abstract: The ratio of fast- and slow-twitch fibers in human skeletal muscle is variable and largely determined by genetic factors. In this study, we investigated the contribution of microRNA (miRNA) in skeletal muscle fiber type composition. The study involved biopsy samples of the vastus lateralis muscle from 24 male participants with distinct fiber type ratios. The miRNA study included samples from five endurance athletes and five power athletes with the predominance of slow-twitch (61.6–72.8%) and fast-twitch (69.3–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 104 publications
0
6
0
Order By: Relevance
“…Only the increased miR-206-3p level was affected in Wt mice and did not change in Tg mice. More importantly, the increase in miR-206 levels has been observed in power athletes with fast-twitch fiber predominance [35]. Given the training effect in Wt mice and training-induced phenotypic maladaptation in Tg mice, our data likely suggest that increased miR-206-3p levels may play an important role in resistance exercise-induced hypertrophy and may be linked to the interference effect.…”
Section: Discussionmentioning
confidence: 51%
“…Only the increased miR-206-3p level was affected in Wt mice and did not change in Tg mice. More importantly, the increase in miR-206 levels has been observed in power athletes with fast-twitch fiber predominance [35]. Given the training effect in Wt mice and training-induced phenotypic maladaptation in Tg mice, our data likely suggest that increased miR-206-3p levels may play an important role in resistance exercise-induced hypertrophy and may be linked to the interference effect.…”
Section: Discussionmentioning
confidence: 51%
“…In their study including 28 juvenile Iberian pigs fed either a control or a high-fructose, high-fat (HFF) diet for 10 weeks, H.C. Spooner et al [ 70 ] demonstrated that the HFF diet resulted in decreased IMCL fat content and in the formation of less oxidative skeletal muscle phenotype, reflecting the disturbed ability of skeletal muscles to use lipids as a fuel. These changes were similar to the effects of detraining or muscle atrophy, indicating the reduced capacity of muscles to perform endurance-type exercises [ 71 ]. These effects may be followed by a long-term decrease in muscle mass and strength.…”
Section: Skeletal Muscles In Obesitymentioning
confidence: 68%
“…In previous studies, miR-1, miR-133a, miR-133b and miR-206 have been reported to be myomiRs, i.e., miRNAs that are highly expressed specifically in muscle ( 43 46 ). In particular, miR-206 exhibits muscle-specific expression characteristics ( 43 , 45 , 47 ), and miR-133b is downregulated in the plasma of patients with sarcopenia ( 24 ). A previous study showed that the expression levels of mature miRNAs and their precursors are not positively correlated ( 14 ).…”
Section: Discussionmentioning
confidence: 99%